Genome sizes in diploid and allopolyploid Arachis L. species (section Arachis) - Samoluk, Sergio Sebastián (2015)
Fil: Samoluk, Sergio Sebastián. Universidad Nacional del Nordeste. Facultad de Ciencias Agrarias; Argentina.